Pengaruh Bauran Pemasaran dan Persepsi Konsumen terhadap Keputusan Pembelian Sayuran Hidroponik (Studi Kasus pada Kebun Hidroponik Griya Botani) - Amilia Eka Putri; Sri Tjondro Winarno; Dona Wahyuning Laily (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
The high market demand for vegetables guaranteed to be safe, clean, and of excellent quality is increasingly in demand by modern society. The higher demand for hydroponic vegetables opens up promising business opportunities for farmers, so hydroponic vegetable producers need to understand the factors influencing consumer purchasing decisions to win fierce market competition. This study aimed to analyze the effect of mixed marketing and consumer perceptions on purchasing decisions for hydroponic vegetables at Kebun Hidroponik Griya Botani. The research was conducted from  February until  April 2024 at Jl. Perum Pondok Mutiara, Banjarbendo, Kec. Sidoarjo, Kab. Sidoarjo, Central  Java. The number of respondents in this study was 50, selected by chance (accidental sampling), and the data obtained were analyzed using SEM PLS 8.0. The results showed that the 7 P mixed marketing (product, price, place, promotion, people, physical evidence, and process) significantly positively affected purchasing decisions for hydroponic vegetables. Meanwhile, consumer perception (health awareness and food safety) had no significant effect on purchasing hydroponic vegetables. So, Kebun Hidroponik Griya Botani must regularly participate in events, such as product marketing or other festivals, in order to educate the public or consumers about the benefits and advantages of hydroponic vegetables from cultivation to post-harvest through word of mouth and distributing pamphlets so that people and consumers are interested in buying hydroponic vegetable products.